Biotechnological valorization of oilseed cakes: Substrate optimization by simplex centroid mixture design and scale‐up to tray bioreactor. (9th September 2022) - Sousa, Daniel; Salgado, José Manuel; Cambra‐López, Maria; Dias, Alberto; Belo, Isabel
Abstract: Sunflower (SFC), rapeseed (RSC), and soybean cakes (SBC) are examples of oilseed cakes (OC) used in animal feed. Bioprocessing of these OC by solid‐state fermentation (SSF) aims to boost OC applications in feed and other industries by reducing antinutritional factors and releasing enzymes and antioxidants. A simplex centroid design was performed to optimize the substrate composition of SFC, RSC and SBC mixtures that maximize lignocellulolytic enzymes production by SSF with Aspergillus niger and consequently improve the nutritional properties of OC. Enzyme production by SSF of OC mixtures exceeded the activity values obtained using a single oilseed cake. A mixture composed of 50% (w/w) RSC and SBC was found to be the optimum substrate. The scale‐up from flasks to tray‐type bioreactors demonstrated SSF reproducibility, leading to the production of 299 U g −1 cellulase, 1476 U g −1 xylanase, 191 U g −1 β ‐glucosidase and 220 U g −1 protease. The obtained enzymatic extract also presented antioxidant activity (around 50 μmol Trolox equivalents/g). This study demonstrated that bioprocessing of OC mixtures through SSF is an effective approach to obtain value‐added products with applications as feed or feed additives and to increase the liberation of bioactive compounds with applications in the feed, food, cosmetic and pharmaceutical industries. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.